Tailored physiotherapeutic intervention study for musculoskeletal disorders among video display terminal users : Tailored intervention for MSD - Larese Filon, Francesca; Dusefante, Alex; Peresson, Maria; Flego, Annamaria; Dallan, Gabriele; Cacciatori, Barbara (La Medicina del Lavoro, 2022)
Background: Musculoskeletal disorders represent one of the most common complains among video display terminal (VDT) users and are responsible for an important burden of disease in white collars. Methods: From May 2017 to March 2018, 69 VDT users working at Trieste hospitals were recruited for a training session aimed to reduce musculoskeletal disorders in white collars workers. Thirty-three were assigned to the intervention group, whereas 36 comprised the control group. The intervention group received three personalized 1-hour-one-to-one sessions with a physiotherapist and a thorough evaluation of their workstation. Data were collected at baseline (T0), at 2 months (T1) and at 6 months (T2) using a standardized questionnaire and analyzed with the software STATA. Results: Overall pain significantly decreased in cases at T1 and T2 (p < 0.05). Headache significantly decreased in cases at T1 (p < 0.05). Body awareness significantly increased in cases both at T1 and T2 (p < 0.05). Headache was positively correlated with an increased perception of pain (Coef 6.85, CI95% 3.2-10.5; p < 0.001), while the intervention determined a significant reduction of overall pain during the follow up (OR 0.97, IC 0.95-0.99, p = 0.013). Cases showed a significant increase of the cranial-vertebral angle at the 6 months follow up (p < 0.05). Conclusion: A tailored physiotherapeutic intervention has showed a statistically significant decrease in osteoarticular pain and an increased body awareness in VDT users undergoing a personalized training session.v